Pelatihan Kreativitas, Desain Berpikir, dan Pembuatan Media e-learning Inovatif Berbasis DI-VAKSIN (Digital, Visual, Auditori, Kinestetik, Sinkron) untuk Guru SMP Negeri 1 Sooko Mojokerto - Elfia Nora; Sopiah Sopiah; I Nyoman Suputra; Imam Bukhori (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
E-learning media is very useful for teachers in supporting the teaching and learning process in the classroom. Apart from having to understand how to use various existing e-learning media, teachers can also design digital e-learning media that are adapted to student learning styles consisting of Visual, Audiotorial and Kinesthetic as well as Asynchronous and synchronous. E-learning media products designed from the results of teacher training are in the form of Android-based applications, consisting of Visual, audio, Kinesthetic menus, and all Materials. This application contains material and assignments on all subjects at SMP Negeri 1 Sooko, Mojokerto Regency.